Zinc Influx Restricts Enterovirus D68 Replication - Liu, Shunan; Cao, Xia; Guo, Haoran; Wei, Wei (Frontiers in Microbiology, 2021)
Enterovirus D68 (EV-D68) is a respiratory viral pathogen that causes severe respiratory diseases and neurologic manifestations. Since the 2014 outbreak, EV-D68 has been reported to cause severe complications worldwide. However, there are currently no approved antiviral agents or vaccines for EV-D68. In this study, we found that zinc ions exerted substantial antiviral activity against EV-D68 infection in vitro. Zinc salt treatment potently suppressed EV-D68 RNA replication, protein synthesis, infectious virion production, and inhibited cytopathic effects without producing significant cytotoxicity at virucidal concentrations (EC50=0.033 mM). Zinc chloride (ZnCl2) treatment moderately inhibited EV-D68 attachment. Time-dose analysis of EV-D68 structural protein VP1 synthesis showed stronger suppression of VP1 in the culture medium than that in the cell lysates. Furthermore, a zinc ionophore, pyrrolidine dithiocarbamate, which can transport zinc ions into cells, also enhanced the anti-EV-D68 activity of ZnCl2 treatment. Taken together, our results demonstrated that the enhancement of zinc influx could serve as a powerful strategy for the therapeutic treatment of EV-D68 infections.